Hydrolysable Tannins from Cercidiphyllum japonicum Bark - Lee, Min-Sung; Min, Hee-Jeong; Si, Chuan-Ling; Bae, Young-Soo (Journal of the Korean Wood Science and Technology, 2016)
The EtOAc and H2O soluble fractions of Katsura tree (Cercidiphyllum japonicum Sieb. Et Zucc) bark extracts were chromatographed on a Sephadex LH-20 column with various aqueous MeOH. Gallic acid (1), methyl galate (2), kurigalin (3), 1,2,3,6-tetra-O-galloyl-β-D-glucose (4) and 1,2,3,4,6-penta-O-galloyl-β-D-glucose (5) were isolated from EtOAc fraction. Isocorilagin (6) and methyl galate (2) were separated from H2O fraction. The structure determination was done by 1H and 13C NMR. Of these isolated compounds, methyl galate (2), kurigalin (3) and isocorilagin (6) were isolated, for the first time, from the bark extracts of Cercidiphyllum japonicum.